2023
DOI: 10.3390/ma16051805
|View full text |Cite
|
Sign up to set email alerts
|

Glassy Carbon Open-Celled Foams as a Reinforcement in Polymer Matrix Composites Dedicated for Tribological Applications

Abstract: This work presents the results of a tribological examination of polymer matrix composites reinforced with carbon foams with different porosity. The application of open-celled carbon foams allows an easy infiltration process by liquid epoxy resin. At the same time, carbon reinforcement remains its initial structure, which prevents its segregation in polymer matrix. Dry friction tests, conducted under 0.7, 2.1, 3.5 and 5.0 MPa loads, show that higher friction load results in higher mass loss, but it strongly low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The unfilled epoxy resin sample has the largest volume loss, and the addition of graphite significantly reduces material loss, which extends the service life. This is due to [ 54 , 55 , 56 ] formation of carbon tribofilm, which effectively protects the wear surface from further abrasive damage. An additional advantage of introducing graphite particles into the epoxy resin is the increase in the thermal conductivity coefficient, which is desirable for friction systems because graphite has the ability to effectively dissipate heat and protect the material against early seizure [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The unfilled epoxy resin sample has the largest volume loss, and the addition of graphite significantly reduces material loss, which extends the service life. This is due to [ 54 , 55 , 56 ] formation of carbon tribofilm, which effectively protects the wear surface from further abrasive damage. An additional advantage of introducing graphite particles into the epoxy resin is the increase in the thermal conductivity coefficient, which is desirable for friction systems because graphite has the ability to effectively dissipate heat and protect the material against early seizure [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The obtained tribological test results indicate that the addition of graphite has a beneficial effect on the tribological properties because it reduces the friction coefficient compared to the reference material (epoxy resin), and the tribofilm formed on the surface prevents abrasive wear and seizure. The formation of carbon tribofilm during sliding wear is a well-known mechanism, which has been described earlier in the literature [ 54 , 55 , 56 ]. Upon comparing the obtained results with literature data, it can be concluded that graphite is a cheap filler that reduces the friction coefficient by approximately 30–40%.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous article [40], it was shown that the addition of graphite, creating a carbon tribofilm on the composite surface, leads to reduction in the friction coefficient by over 30% and protects the material against rapid wear. Myalski, in publication [55], observed that carbon reinforcement (carbon foam) acting as a solid lubricant allows for the effective formation of a carbon tribofilm. The observations of the behavior of materials during friction allowed us to confirm the model of the creation of a transfer film.…”
Section: Tribological Resultsmentioning
confidence: 99%